Examining the association between job crafting and work engagement among hospital employees - Marganda Fransiscus Siregar; Della Melisa Ginting; Mukhaira El Akmal; Rianda Elvinawanty (Universitas Ahmad Dahlan, 2026)
This study examined the relationship between job crafting and work engagement among employees at Bina Kasih General Hospital based on the Job Demands–Resources (JD-R) Theory. Although previous research has demonstrated a positive association between job crafting and work engagement, the underlying empirical evidence remains limited, particularly in healthcare contexts in developing countries. A total of N = 122 hospital employees participated in this study using a purposive sampling technique. Data were collected using the Job Crafting Scale based on the Tims and Bakker model and the Work Engagement Scale based on the Schaufeli and Bakker framework. Both instruments showed good internal consistency (α = 0.920 for job crafting; α = 0.849 for work engagement). Data were analyzed using Pearson product-moment correlation via IBM SPSS Statistics 22. The results revealed a significant positive relationship between job crafting and work engagement (r = 0.735, p < .001), indicating that employees who actively modify and optimize their work tend to demonstrate higher levels of work engagement. These findings contribute to the extension of the JD-R model and provide practical implications for enhancing employee engagement in hospital settings through the promotion of job crafting behaviors.